Development of a collaborative research framework: the example of a study conducted by and with a First Nations, Inuit and Métis womens's community and their research partners - Jull, Janet; Giles, Audrey; Boyer, Yvonne; Minwaashin Lodge- The Aboriginal Women's Support Centre; Stacey, Dawn (Université d'Ottawa | University of Ottawa, 2016)
The lack of research that effectively addresses inequity within Canadian society is an indicator of the failure of mainstream research approaches and practices to engage with all populations. This paper describes the development of a collaborative framework defined by a First Nations, Inuit and Métis women’s community members and its research partners as ethical, useful and relevant. There were two essential phases in negotiating a collaborative framework for a community- research partnership and the steps in a community-based participatory approach described: 1) establish guiding features of a collaborative framework by forming an advisory group, developing ethical guidance, agreeing upon underlying theoretical concepts for the research study; and 2) engage in research actions that support co-creation of knowledge throughout study processes. The case study example used to illustrate the collaborative framework was conducted by and with a First Nations, Inuit and Métis women’s community and research partners to culturally adapt a health decision-making strategy. A community-based participatory research approach fostered engagement among community and research participants and directed community-research collaboration. The collaborative framework structured ongoing negotiations within the community-research partnership to ensure that ethical obligations to research participants and the broader community were met and goals of the study achieved.
Keywords: research; collaborative; community; First Nations; Inuit; Métis; decision making; equity; ethics